2022
DOI: 10.3389/fpubh.2022.1003007
|View full text |Cite
|
Sign up to set email alerts
|

Social media use in higher education: Building a structural equation model for student satisfaction and performance

Abstract: Social media utilization at the student-level has become more prevalent contemporary higher education. Hence, this study is aimed at developing a specific model, along with the behavioral intention to use, to explore educational quality, actual social media use, and task-technology fit that affects student satisfaction and performance impact through examining the synergies of constructivism, user acceptance and usage of information technology, and technology acceptance. To test, a survey was administered to 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 113 publications
3
25
0
2
Order By: Relevance
“…The findings of the present study are consistent with prior research that has focused on undergraduate students, demonstrating that perceived ease of use plays a central role in moulding these individuals' attitudes towards social media usage (Al-Rahmi et al ., 2022a, b; Yuan et al ., 2021; Cheta and Yinka, 2016). Within this framework, it has been demonstrated that perceived ease of use exerts a positive impact on behavioral intention to engage with social media among individuals who are pursuing higher education (Dumpit and Fernandez, 2017; Siddhartha et al ., 2020; Cheta and Yinka, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the present study are consistent with prior research that has focused on undergraduate students, demonstrating that perceived ease of use plays a central role in moulding these individuals' attitudes towards social media usage (Al-Rahmi et al ., 2022a, b; Yuan et al ., 2021; Cheta and Yinka, 2016). Within this framework, it has been demonstrated that perceived ease of use exerts a positive impact on behavioral intention to engage with social media among individuals who are pursuing higher education (Dumpit and Fernandez, 2017; Siddhartha et al ., 2020; Cheta and Yinka, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This research makes a significant contribution to comprehending the prevalent determinants of PEOU and PU of social media in learning through digital technology in higher education settings. The contribution of undergraduate social media use is crucial, as PEOU and PU positively impacted academic performance in past studies (Al-Rahmi et al ., 2022a, b). The findings contribute to the gap in digital learning in higher education that reflects on the dual effect of social media, positive impact that looks at facilitating academic endeavors or negative impact that leads to maladaptive usage of social media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is clear that the various technologies and e-learning systems employed at universities are related to the degree of performance and ongoing purpose to use elearning systems, either directly or indirectly [7]. According to research on the possibility of improving teaching and learning results by [23] and [25], an e-learning system should be developed using a variety of constructs to manage student learning and a persistent intention to employ e-learning for teaching outcomes.…”
Section: Task-technology Fit (Ttf)mentioning
confidence: 99%
“…According to a number of study findings ( Al-Rahmi et al, 2015b ; Hong et al, 2017 ), user satisfaction is favorably correlated with the intention to reuse e-learning systems and MOOCs. In order to determine whether or not users would continue to utilize the e-learning system, Al-Rahmi et al, (2015c , d , 2022a ) investigated key parameters. According to their findings, user perceptions in terms of content and user interface are positively correlated with users’ intentions to continue using the product.…”
Section: Hypotheses Developmentmentioning
confidence: 99%